A polissemia na linguagem não verbal: no caso os emojis - PINHEIRO, Nilma de Jesus Feio (2019)
The study verified the occurrence of polysemy through visual stimuli, emojis searches, which are often done on interaction platforms such as Facebook, Twitter, Menssaggen and, in particular, Watsapp. In this way, the displacement of the polysemic phenomenon from verbal language to non-verbal language is evidenced. In this way, the intention is to generate a reflection about the work, in order to offer a new perspective to approach the polysemic phenomenon. In addition, the work was based on bibliographical reviews with emphasis on studies by Duarte (2003), interview exercises and questionnaire, essential elements for the research exercise. Therefore, the results showedthat the fact that there is a polysemy in the nonverbal language opposite was one of those thatimproved the phenomenon as occurring in verbal language.